SEASONAL INCIDENCE OF MAJOR INSECT PESTS OF GROUNDNUT AND THEIR NATURAL ENEMIES IN RELATION TO METEOROLOGICAL PARAMETERS - G. V. SUNEEL KUMAR (The Journal of Research ANGRAU, 2023)
Seasonal incidence of major insect pests in groundnut was studied during kharif 2015-16 with the variety, Kadiri-6 (K6). The results indicated that the population of groundnut leaf miner (Aproaerema modicella) reached peak in the first week of September with a mean larval incidence of 0.8 plant-1 and the larval population of tobacco caterpillar (Spodopter alitura) was more abundant on the crop during second week of October with a mean incidence of 9.3 plant-1. Aphid (Aphis craccivora) touched the peak in the first week of September with a mean population of 8.8 aphids top 2 cm shoot-1; whereas, leaf hopper(Empoasca kerri) attained the peak in the second week of September with a mean population of 10.6 three leaves-1 plant-1. Maximum activity of thrips, Scirtothrips dorsalis (Hood) was recorded in the second week of October with a mean of 4.8 terminal-1. Leaf miner, leafhopper and aphids showed positive correlation with rainfall (r= 0.120, 0.158 and 0.121, respectively). In case of larval (r= -0.075) and adult (r= -0.103) populations of S. litura, adult catch of H. armigera (r= - 0.299) and thrips (r= -0.105) negative correlation were observed with rainfall. Larval and adult populations of S. litura and thrips showed positive correlation to both minimum (r=0.196, 0.159, 0.179) and maximum temperature (r=0.067, 0.266, 0.095, respectively). However, leaf miner, leafhopper, aphid populations and H. armigera adult catch showed negative correlation for maximum temperature (r= -0.008, -0.250, -0.014 and -0.148) and positive correlation with minimum temperature (r= 0.084, 0.663, 0.646 and 0.127, respectively). With respect to relative humidity, all the pest populations have showed negative correlation, however, leaf hopper and aphids only recorded significance at 5% with morning RH (r= -0.680 and -0.583). Peak activity of predators were recorded a week after the pest populations attained their peak.The populations of three predators’viz., coccinellids, spiders and syrphid fly maggots were positively correlated with all the pest populations